Usefulness evaluation of the metadata schema of the digital asset management system of Pioneer Studios digital archive - Matuguinas, Dessa S. (2016)
Metadata plays a huge role in archiving digital images. The importance of metadata is highlighted in its indispensability within the priced of locating digital images. Thus the selection of metadata elements to include is highly important. However, due to a number of different existing standards, choosing useful metadata elements that streamline access is quite difficult. To determine which metadata elements are useful for searching and retrieval it is vital to know the use-patterns and preference of the would-be users during the process of searching / retrieving digital images. The purpose of this study is to assess metadata elements of the digital asset management system of Pioneer Studios that facilitate the process of searching and retrieval. Due to the nature of their courses, or pursued degrees, that deal, primarily, in photos and images, fine arts and art studies students of UP Diliman are the respondents of this study. According to the results of the survey, artists and art studies students search for artwork images in random manner; this means that the respondents are more prone to use descriptive metadata elements rather than bibliographic metadata elements. Technical metadata, on the other hand, is hardly used. The results of this research will be used as a foundation for other studies that deal with the streamlining of access to images in the digital image archive of Pioneer studios. Also, the institution will find the study useful as a basic guide regarding their current collection. Lastly, the study may be used as basis or preliminary framework, for the creation of a digital archive.